2020
DOI: 10.3390/ijms21228645
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α-Synuclein Oligomers in Parkinson’s Disease

Abstract: α-synuclein (α-syn) is a protein associated with the pathogenesis of Parkinson’s disease (PD), the second most common neurodegeneration disease with no effective treatment. However, how α-syn drives the pathology of PD remains elusive. Recent studies suggest that α-syn oligomers are the primary cause of neurotoxicity and play a critical role in PD. In this review, we discuss the process of α-syn oligomers formation and the current understanding of the structures of oligomers. We also describe seed and propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 116 publications
0
88
0
1
Order By: Relevance
“…HSV-1 in not suggested to only be involved in PD, but is also suspected to participate to the pathogenesis of Alzheimer's disease (AD). Thus: (1) HSV-1 specific IgG titers and avidity are higher in AD patients compared to healthy controls [29,30]; (2) HSV-1 antibody avidity associates with AD conversion in individuals with mild cognitive impairment (MCI) [31]; (3) HSV-1 specific IgG titers positively correlate with brain grey matter volumes and cortical thinning in AD patients [30,32]; (4) in vitro and animal studies showed that HSV-1 can cause accumulation of amyloid-beta and hyperphosphorylated tau, key factors of the disease [33][34][35]; (5) an in vitro study on human neural cells showed that HSV-1 directly impairs autophagy, reducing amyloid-beta degradation [36].…”
Section: Introductionmentioning
confidence: 99%
“…HSV-1 in not suggested to only be involved in PD, but is also suspected to participate to the pathogenesis of Alzheimer's disease (AD). Thus: (1) HSV-1 specific IgG titers and avidity are higher in AD patients compared to healthy controls [29,30]; (2) HSV-1 antibody avidity associates with AD conversion in individuals with mild cognitive impairment (MCI) [31]; (3) HSV-1 specific IgG titers positively correlate with brain grey matter volumes and cortical thinning in AD patients [30,32]; (4) in vitro and animal studies showed that HSV-1 can cause accumulation of amyloid-beta and hyperphosphorylated tau, key factors of the disease [33][34][35]; (5) an in vitro study on human neural cells showed that HSV-1 directly impairs autophagy, reducing amyloid-beta degradation [36].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that α-syn oligomers are the primary cause of neurotoxicity and play a critical role in PD, similar to that of Aβ oligomers in AD [90]. Emerging evidence suggests that small soluble α-syn oligomers are the most toxic species among the forms of α-syn aggregates and that size and topological structural properties are crucial factors for oligomer-mediated toxicity, involving the interaction with either neurons or glial cells [91].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…DS is caused by heterozygous loss-of-function mutations in the SCN1A gene, which encodes the pore-forming alpha subunit of the voltage-gated sodium channel Nav1.1. Majority of DS mutations lead to insufficient levels of SCN1A protein in inhibitory neurons where it is preferentially expressed ( XY. Du et al, 2020 ).…”
Section: Nbts In Orphan Neurological Disordersmentioning
confidence: 99%